Influence of Lauryl Betaine on Bulk Foam Stability and Apparent Viscosity in Porous Media - HASSAN, SYED ASAD (2019)
Foam has been studied as a gas mobility control agent for several decades. One of the major problems in the application of foam as a gas mobility control method is the stability of the foam.